Hypoparathyroidism is associated with bladder dysfunction, a preliminary study - Işılay Taşkaldıran; Şerife Mehlika Kuşkonmaz; Aykut Uçar; Arif Bedirhan Bayraktar; Çağrı Öktem; Berat Cem Özgür (Scientific Reports)
Abstract Hypoparathyroidism (HP) after head and neck surgery leads to hypocalcemia and related comorbidities. This study aimed to evaluate bladder functions using uroflowmetry and lower urinary tract (UT) function questionnaires in patients who developed postoperative HP. This study included 30 premenopausal women who developed postoperative HP and 30 healthy control groups. Bladder functions were evaluated using uroflowmetry, the Overactive Bladder-Validated 8 (OAB-V8) form, and the Interstitial Cystitis Symptom Index/Interstitial Cystitis Problem Index (ICSI/ICPI) questionnaire. ICSI and ICPI scores and OAB-V8 scores in the postoperative HP group were significantly higher than controls. Patients with postoperative HP had statistically higher post-voiding residue (PVR) values than the controls. A negative correlation was found between the ICSI score, ICPI score, OAB-V8 score, PVR levels, serum calcium and PTH levels. This study demonstrated disturbed lower UT functions in patients with postoperative HP. Bladder dysfunction and lower UT symptoms should be considered in patients with postoperative HP.